2010
DOI: 10.1161/cir.0b013e3181cf3117
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Wall Hematoma/Dissection After Mitral Valve Replacement

Abstract: A 63-year-old woman with a significant history of rheumatic mitral stenosis/regurgitation, tricuspid regurgitation, atrial fibrillation, and giant left atrium (LA; 90 mm in diameter) underwent mitral valve replacement with a mechanical valve, tricuspid annuloplasty, and LA appendage closure. The mitral valve was approached by a conventional left atriotomy from the right side of the LA. The postoperative course was uneventful initially, and the patient was extubated on postoperative day 1. On postoperative day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…To the present authors’ knowledge, this is the first reported case of left atrial intramural hematoma (LAIH) following ablation of a left posterolateral accessory pathway using a retrograde aortic approach. LAIH, also commonly referred to as left atrial dissection, has been most frequently associated with mitral valve repair and replacement (in more than one-half of cases) as well as post-RFA for atrial fibrillation and left atrial tachycardia ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Up to 10% of cases may occur spontaneously ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the present authors’ knowledge, this is the first reported case of left atrial intramural hematoma (LAIH) following ablation of a left posterolateral accessory pathway using a retrograde aortic approach. LAIH, also commonly referred to as left atrial dissection, has been most frequently associated with mitral valve repair and replacement (in more than one-half of cases) as well as post-RFA for atrial fibrillation and left atrial tachycardia ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Up to 10% of cases may occur spontaneously ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 The 2nd most frequent cause of LA wall dissection is blunt chest trauma as a sequela of external cardiac massage or a motor vehicle accident.…”
Section: Discussionmentioning
confidence: 99%
“…The close proximity of the circumflex artery and coronary sinus to the posterior wall of the left atrium, AV groove and mitral annulus is another important factor for the development of Lad during coronary artery bypass grafting surgeries. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%